Sample exercises for testing vocabulary skills in the first year high school - Cabredo, Josefa Bejo 1944- (1972)
Sample exercises for testing students' vocabulary skills in the first year high school level are presented in the study. The Handbook for Testing English in Secondary Schools, a 1970 Summer project of the Bureau of Public Schools, Secondary Education Division, is the main reference in the selection of vocabulary tests found in this study for which sample test exercises have been made.
Vita.
Thesis (M.A. Reading Education)--University of the Philippines, Diliman.
Keywords: Reading (Secondary) -- Philippines -- Legazpi City (Albay).; English language -- Study and teaching (Secondary).; English language -- Textbooks; Vocabulary tests -- Philippines -- Legazpi City (Albay).